Factors Influencing the Earning Capacity of NCBs in Bangladesh: An Evaluation - Neogy, Taposh Kumar; Aishi, Aditi Sonia (American Journal of Trade and Policy, 2018)
Recently, Bangladesh economy has been experiencing a rapid growth in most of the sectors of economic activities. For the attainment of higher levels of economic development, Bangladesh is trying to achieve and maintain high rates of economic growth. Economic development and the development of banking sector are closely related. The banks especially state-owned commercial banks have been playing significant role to the development process. The state-owned commercial bank makes the profit through banking business. But there are some factors those influence the profit volume of state-owned commercial banks. The objective of the study is to identify those influencing factors and examine the opinions of the respondents regarding the factors. It is also attempted to see whether there is any significant difference of opinions among the respondents regarding various influencing factors of profit volume using null hypotheses, χ2 test and ANOVA test. It is found that the identified factors include attitude of government, maintenance of privacy, proper control, efficiency of management, conflict in management, creativity and innovation and job satisfaction. The study also revealed that the respondents are unanimous regarding the various influencing factors of profit volume.
Keywords: Earning Capacity; NCBs; Bangladesh